A VIEW OF MULTIDISCIPLINARY HEALTH PROMOTION TEAMS : TEAMWORK IN HEALTH PROMOTION - Boričić, Katarina; Tošić, Mirjana; Šiljak, Slađana (Srpski medicinski časopis Lekarske komore, 2023)
The success of modern health promotion programs, which have been brought about by political decision at the local, national, and international levels, depend on the effectiveness of health promotion teams. In this article, the multidisciplinary approach is reviewed as a modern approach to teamwork for health promotion, which is a prerequisite for effective health promotion. The multidisciplinary approach includes a wide range of experts in public health, with different knowledge, qualifications, and skills, brought together to contribute to the provision of health promotion services from their own perspective.
Keywords: health promotion; multidisciplinary; teamwork